Neuroprotective Role of Transchalcone in Parkinson‘s Disease through AMP-activated Protein Kinase-mediated Signaling Pathway - Yao Cheng; Shaik Althaf Hussain; Turki Mayudh Alrubie; Xiaomin Zhang (Journal of Physiological Investigation)
Parkinson’s disease (PD) is a gradually worsening neurodegenerative condition marked by the deterioration of dopaminergic neurons, motor dysfunction, and mitochondrial dysfunction. Trans-chalcone, a natural flavonoid, has shown promise in various disease models because of its antioxidant and anti-inflammatory features. This study investigates the neuroprotective effects of transchalcone in a rat model of PD, focusing on its impact on the activation levels of AMP-activated protein kinase (AMPK) signaling pathway, sirtuin1 (SIRT1) and peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α) proteins, and mitochondrial-inflammatory responses. Male Sprague Dawley rats were allocated into five groups Control, Control plus transchalcone, PD, PD plus transchalcone, PD plus compound-C, and PD plus Compound-C and trans-chalcone. PD was induced using intranigral 6-hydroxydopamine injection. Trans-chalcone (100 μg/kg) and compound-C (20 mg/kg) were intraperitoneally administered daily for 4 weeks in PD rats. Motor function was assessed using rota-rod and grid tests. Striatal dopamine and cytokines (interleukin 1-beta [IL-1 β], IL-10) and p65-nuclear factor kappa-B (NF-κB) levels were measured with enzyme-linked immunosorbent assay. Mitochondrial function was evaluated by fluorometric techniques. The expression of phosphorylated AMPK, PGC-1α, and SIRT1 was analyzed by Western blotting. Trans-chalcone treatment significantly improved motor function, evidenced by increased latency to fall in the rota-rod test and recovered traversal time in the grid test. It also restored dopamine levels, enhanced mitochondrial function (reduced reactive oxygen species levels, increased membrane potential, and adenosine triphosphate production), normalized cytokines (IL-1 β, IL-10) and p65-NF-κB, and upregulated the proteins expression in rats with PD. Inhibition of AMPK activity with compound-C suppressed the neuroprotective impacts of trans-chalcone, highlighting the contribution of AMPK signaling pathway in its mechanism of action. Neuroprotective and mitoprotective impacts of trans-chalcone were mostly mediated through the activation of AMPK-SIRT1-PGC1α pathway. These results indicate that trans-chalcone could be a promising therapeutic agent for PD, warranting further investigation to assess its efficacy and safety in human patients.